Hamka’s neo-sufism in the context modern society - Fathor Rahim; Hasnan Bachtiar (Universitas Negeri Yogyakarta, 2023)
This article purposes to analyze and discuss the Hamka's neo-Sufism idea. It is related and contextualized to various problems that emerge in modern society, especially capitalistic industrialization, and hedonistic culture. This article states that Hamka's neo-Sufism aims to find true happiness and transcendence (ma’rifatullah). Through the practice of Hamka's neo-Sufism, it will protect a Muslim from all temptations for the interests of the accumulation of wealth and the pleasures of worldly life. Neo-Sufism persistently strengthens the spiritual quality of a Muslim, making one always aware of when dealing with changing life contexts.